Inadequate Sampling Rates Can Undermine the Reliability of Ecological Interaction Estimation - Cabella, Brenno [UNESP]; Meloni, Fernando; Martinez, Alexandre S. (Mdpi, 2019)
Cycles in population dynamics are abundant in nature and are understood as emerging from the interaction among coupled species. When sampling is conducted at a slow rate compared to the population cycle period (aliasing effect), one is prone to misinterpretations. However, aliasing has been poorly addressed in coupled population dynamics. To illustrate the aliasing effect, the Lotka-Volterra model oscillatory regime is numerically sampled, creating prey-predator cycles. We show that inadequate sampling rates may produce inversions in the cause-effect relationship among other artifacts. More generally, slow acquisition rates may distort data interpretation and produce deceptive patterns and eventually leading to misinterpretations, as predators becoming preys. Experiments in coupled population dynamics should be designed that address the eventual aliasing effect.
Keywords: temporal aliasing effect; ecological methods; sampling rates; cyclic dynamics; predator-prey system; population biology